Implementasi Program Audit Kasus Stunting di Wilayah Kerja Puskesmas Guntur 1 - Muhim Sajida Tholfa; Fitri Indrawati (Jurnal Medika Nusantara, 2024)
The prevalence of stunted toddlers in Demak Regency in 2021 is 25,5%. This prevalence figure is above the threshold (cut off) that has been universally agreed upon. There are 7 Community Health Centers that are the locus of stunting in Demak Regency, including Guntur 1 Community Health Center. This research aims to determine the implementation of the stunting case audit program in the Guntur 1 Community Health Center working area. This study uses a qualitative method. The informants in this research consisted of the Head of Guntur 1 Community Health Center, the Guntur 1 Community Health Center Nutritionist, the Village Midwife, Cadres from Temuroso Village and Tlogorejo Village, as well as mothers of stunted and non-stunting toddlers. Data collection through in-depth interviews, observation and documentation. The result of this research indicate that the implementation of the stunting case audit program in the Guntur 1 Community Healt Center working area is quite good. The actor categories, decision making, benefits, program implementers, actor strategies, action programs, communication and bureaucratic structures are good. In the categories of resources and compliance and responsiveness there are problems and obstacles. The suggestion of this research is for the community health center to increase intervention with the community in preventing stunting.